Using Roundtable Technique to Enhance the Eleventh Grade Students' Narrative Writing Achievement at MAN 2 Jember - Ismatullah, Maulidiyah; suharjito, bambang; Andayani T, Made Adi (EFL Education Journal, 2016)
The objectives of this research were to improve the eleventh grade students'narrative writing achievement and their participation by using roundtable technique atMAN 2 Jember in the 2015/2016 academic year. The research design was classroom actionresearch. The subject area of this research was chosen purposively. The research subjectwas the eleventh science 1 which was chosen based on the observation and the previouswriting score from the English teacher. The data were collected by administering thewriting test, observation, interview and documentation. This research was done in 2 cycles.The results in each cycle showed improvement of the students narrative writingachievement and students' active participation. The results in Cycle 2 had met the criteria ofthe success that indicatedthat the use of roundtable technique could improve the students'narrative writing achievement and also their active participation in teaching and learningprocess of writing at MAN 2 Jember